Irrational Use of Selected Herbal Medicines During Pregnancy: A Pharmacoepidemiological Evidence From Yemen - Mansoor Ahmed; Mansoor Ahmed; Mansoor Ahmed; Mansoor Ahmed; Jung Hye Hwang; Jung Hye Hwang; Jung Hye Hwang; Mohammed Nasr Ali; Mohammed Nasr Ali; Shafekah Al-Ahnoumy; Shafekah Al-Ahnoumy; Dongwoon Han; et al. (Frontiers Media S.A., 2022)
Background: Recent research indicates irrational use of herbal medicine (HM) during pregnancy that can be harmful to the mother and development of baby. However, no study has been conducted to explore the use of HM among pregnant women in a conflict region.Methods: This was a cross-sectional research conducted in July and August in the year 2017, at three hospitals in Sana'a, Yemen. Postpartum women were interviewed via the structured instrument to collect data on patterns of HM used during pregnancy.Results: A total of three hundred postpartum women participated in the study, with 59.3% (178) of them using at least one modality of HM in the previous pregnancy. Cinnamon (Cinnamomum verum L), ginger (Zingiber officinale Z), barley (Hordeum vulgare P), and garlic (Allium sativum A) were the most commonly used HM. Statistical analysis showed that consumers of HM had a higher rate of caesarian section and complications during and after the delivery.Conclusion: Consumption of HM during pregnancy was high including contraindicated modalities such as cinnamon (C. verum L) and barley (H. vulgare P). The use of potentially harmful modalities and association with complications pose a threat to the well-being of mothers and newborns. Further studies in this area will be helpful to generate evidence for the rational use of HM during pregnancy.